Antifungal Resistance in Candida Species: A Bit from the Totality - Janabi, Ali Abdul Hussein S. AL (Anti-Infective Agents, 2025)
Resistance to antifungals is one of the natural protection processes developed by fungi to promote their persistence. Exposure of fungi to these agents over long periods due to improper prescription or a contaminated environment increases the resistance problem. Microbiology related to fungal species and clinical settings related to the therapeutic failure of antifungal drugs are two concepts used to define resistance. The minimum inhibitory concentration (MIC) measurement is the common criterion for determining antifungal resistance. Candida spp. is the most common group of fungi that has developed resistance to different antifungal agents. C. albicans has shown resistance to numerous antifungal agents from this genus, followed by non-albicans Candida (NAC). The majority of resistance is to the azole group of antifungal agents through various mechanisms. Resistance to echinocandins is also reported in many species of Candida, while resistance to polyene has been observed in rare cases. The mechanism of resistance action is generally related to a genetic mutation, which changes the mechanisms of diffusion, fungal structure, and drug degradation. Biofilm formation also contributes to antifungal resistance. Current information on the nature and mechanism of antifungal resistance in Candida spp. is briefly presented in this review.
Keywords: Candida